Biología reproductiva de Potamorhina altamazonica (Cope, 1878) “llambina” y Prochilodus nigricans (Agassiz, 1829) "boquichico", en la cuenca media del río Putumayo, Loreto - Perú - Yumbato Castro, Hiro Paolo (2022)
This research was conducted in the middle basin of the Putumayo River from November 2020 to October 2021. The objective of the work was to establish the reproductive biology of Potamorhina altamazonica "llambina" and Prochilodus nigricans "boquichico" in their natural environment. Sampling was carried out through records of fishing landings from different ports, collection centers and through exploratory fishing activities in fishing areas near the town of El Estrecho (02°26'29.9" S, 72°40'11.3" W). A total of 336 llambinas and 253 boquichicos, were analyzed for a period of 12 months, collecting data in the early morning hours (4:30 a.m. and 8:30 a.m.), while monitoring of the lakes was carried out between 17:00 pm and 6:00 am. Biometric data (LS, LH, LT and weight) were recorded for both species, followed by the recognition of the gonads by direct observation, which followed the methodology proposed by Lavaestu (1971), Riofrío (2011) and Flores (2013). Among the main results, it was observed that the overall sex ratio of llambina was 1.9:1 in favor of females and boquichico was determined to be 1.9:1 in favor of females. Fifty percent of the llambina population showed their first sexual maturity size at 22.5 cm and 22.1 cm in total length for females and males, respectively. The boquichico population reached first sexual maturity at 25 cm total length for females and 25.2 cm for males. The gonadosomatic index of llambina was higher between October and February, while boquichico was higher between November and March, respectively. It is concluded that reproductive parameters determined significant differences in sexual structure (x2 0.05), the sizes at first sexual maturity propose measures of fishery regulation and that the reproductive period of both species is influenced by the hydrological period of the Putumayo River.